Metaphorical Conceptualization of Sadness in Wolaita - F. F. Faltamo; D. A. Jekale; M. T. Tsegaye (Дискурс профессиональной коммуникации, 2024)
This study investigates the metaphorical conceptualization of sadness in Wolaita, a language spoken by over 1.6 million people in Ethiopia, from a cognitive-linguistic perspective. Grounded in Conceptual Metaphor Theory (CMT), the research explores how the Wolaita people express sadness through linguistic metaphors and compares these with findings from well-studied languages such as English, Amharic, and Agnwa. The study aims to identify linguistic metaphors for sadness in Wolaita, describe their universal and culturally specific bases, and contribute to the debate on the universality versus culture-specificity of emotion conceptualization. Using qualitative methods, including data elicitation, introspection, and analysis of written and spoken texts, the study examines metaphorical expressions of sadness in Wolaita. Data sources include Wolaita-language textbooks, a bilingual dictionary, idioms, audio-visual materials, and native-speaker intuitions. The analysis identifies conceptual mappings between source domains (e.g., pain, fluid, journey) and the target domain of sadness. The findings reveal that sadness in Wolaita is conceptualized through metaphors such as “sadness is pain,” “sadness is fluid,” “sadness is down,” “sadness is enemy,” “sadness is burden,” “sadness is journey,” “sadness is food,” and “sadness is gift.” These metaphors reflect the Wolaita people’s perception of sadness as an undesirable emotion, with cultural peculiarities such as the use of spoiled foods and impure fluids to represent its intensity. The study demonstrates that although sadness is universal at a basic level, its complex conceptualizations exhibit cultural specificity. This research contributes to cognitive linguistics and emotion studies by providing empirical evidence from an understudied language. It highlights the interconnection between universal human experiences and culturally shaped metaphors, enriching our understanding of the universality versus culture-specificity debate and underscoring the importance of linguistic diversity in emotion research.